The social work criminal law policy reduces the overcapacity of correctional institutions - Romi Saputra (Faculty of Law, University of Merdeka Malang, 2022)
This study discusses the imposition of a sentence against a person who commits a crime which is a very important part of realizing a good criminal justice system, in this case, the judge must be able to choose the right type of punishment for the perpetrator. The alternative to imprisonment, in this case, social work punishment, provides for the fact that prison sentences are increasingly being criticized due to humanitarian considerations, philosophical considerations, and economic considerations. Criticism of the negative consequences of imprisonment has given rise to thoughts of looking for an alternative to imprisonment, even though imprisonment can be justified in terms of crime prevention and public safety. Social work criminal acts for perpetrators of minor crimes can fulfill elements of development and provide protection to society. Guidance elements that are oriented toward individual criminal offenders who are convicted of social work offenders are protected from negative impacts such as being labeled as offenders by society and loss of self-confidence.How to cite item:Â Saputra, R. (2022). The social work criminal law policy reduces the overcapacity of correctional institutions.Â Jurnal Cakrawala Hukum, 13(3), 308-315. DOI:https://doi.org/10.26905/idjch.v13i3.6512.